Economic impact of flood damage based on inter-regional input–output analysis: a case of local rivers in the Nakdong River basin - Jeonghyun Yang; Kichul Jung (Environmental Research Communications)
This study evaluated the economic impacts of flood damage in the Nakdong River basin, South Korea, by quantifying both direct and indirect damages caused by local riverine floods. We used a risk-based approach to calculate direct damages as expected annual damages across five critical asset categories: residential buildings, agricultural assets, vehicles, human impact, and industrial assets. To assess indirect damages, we utilized an inter-regional input–output model, capturing the cascading economic effects across various industries and regions. Our analysis revealed pronounced spatial heterogeneity, identifying industrial and residential buildings as the most vulnerable asset categories. Indirect damages were predominantly concentrated in the manufacturing and service sectors, highlighting their critical roles within regional and national economies. Regions such as Seoul and Gyeonggi Province exhibited substantial indirect damages, revealing the economic interdependencies between flood-affected and nonaffected areas. These findings emphasize the need for spatially nuanced and sector-specific flood risk management strategies. Moreover, this study indicates the importance of integrating forward-looking climate and socioeconomic projections into flood defense policies to address the increasing risks posed by climate change. The results provide actionable insights for policymakers, advocating for enhanced flood resilience to effectively mitigate future economic risks.